Strategies for sustainable upgrading in global value chains: The Tunisian textile and apparel sector - Jan Grumiller; Shamel Azmeh; Cornelia Staritz; Werner Raza; Hannes Grohs; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2018)
This policy note presents policy recommendations for a sustainable development strategy for the Tunisian textile and apparel (T&A) sector in the context of the ongoing negotiations on the Deep and Comprehensive Free Trade Agreement (DCFTA) between Tunisia and the EU. Against the backdrop of economic crisis and decreasing apparel exports to the EU, support for the T&A industry could be an important way to help reinvigorate the economy. A sector development strategy should primarily focus on functional and product upgrading potentials, linkage development as well as on export market and product diversification.
Keywords: 330